Makna Filosofis Iwel-iwel dalam Selamatan Bayi di Jawa: Kajian Linguistik Antropologis - Wulandari, Ari (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This research aims to describe the philosophical meaning of “iwel-iwel”, a traditional Javanese food, using an anthropological linguistic approach with contextual design. Data analysis was carried out by collecting data through interview, observation, note taking and documentation techniques. After that, the process of interview transcription and notes was carried out, followed by the process of reading and analyzing the data. From data analysis, the author obtained the origin of the words and the philosophical meaning of “iwel-iwel” that were then scientifically interpreted in the discussion under the related theories and approaches. The results of this research proved that “iwel-iwel” has philosophical meanings in accordance with the values of local Javanese wisdom. “Iwel-iwel” came from the Javanese word “cemiwel” which means excited; the Arabic word “waliwalidaya” which means parent; and part of the saying “laa ilaha illallah” which means there is no God but Allah. At least “iwel-iwel” contained 10 philosophical meanings, namely (1) a symbol of balance, (2) a representation of calm, (3) a symbol of happiness, (4) respect for tradition, (5) connectedness to nature, (6) a symbol of simplicity, (7) a combination of taste and color, (8) patience and warmth, (9) experience and wisdom, and (10) a symbol of harmony.